Stanje in učinki informatizacije v slovenski javni upravi - Vintar, Mirko (Uporabna informatika (Ljubljana), 2002)
The paper presents teh result of empirical research that intended to ascertainthe level of informatization in public administration and to learn itinformatisation causes organisational and social changes in public sector and to what extent. We focused on existing and wanted situation. We werw interested mainly in the opinions of employees and their view about advantagesand weaknesses that informaton brings. We concentrated on level of information technology(IT), hardware and software, on its impacts on work of individuals and organisation as a whole and on restrictive and stimulating factors that influence the informatisation. The research was carried out by a compehensive questionnaire of employees in public administration. It is one ofthe first research of this type in the e-government field in Slovenia and inthe world as well.
Keywords: analiza; informatizacija; javna uprava; Slovenija